2021
DOI: 10.1002/pon.5838
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy in communication, decision‐making and outcomes among cancer patients, their families and clinicians in India: A multicentre cross‐sectional qualitative study

Abstract: Objective Cancer patients in India prefer full information regarding diagnosis and prognosis, but evidence suggests poor insight. This study aimed to identify the role of health literacy among adult patients living with cancer, their families and health professionals in decision‐making and treatment outcomes in India. Methods This cross‐sectional in‐depth study recruited patients, families and clinicians from three centers. Inductive thematic analysis informed a novel conceptual model. Results We recruited n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
(53 reference statements)
0
5
0
2
Order By: Relevance
“…Therefore, they preferred nondisclosure of information ( 37 , 38 ). These findings were corroborated in a multicentre cross-sectional qualitative study in India, which demonstrated that while clinicians were motivated by professional values to disclose cancer related information, they experienced pressure from family members to conceal information ( 39 ).…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, they preferred nondisclosure of information ( 37 , 38 ). These findings were corroborated in a multicentre cross-sectional qualitative study in India, which demonstrated that while clinicians were motivated by professional values to disclose cancer related information, they experienced pressure from family members to conceal information ( 39 ).…”
Section: Discussionmentioning
confidence: 71%
“…No estudo do Harding et al (2021) o letramento em saúde desempenha um papel importantíssimo na interpretação das informações fornecidas pelos profissionais, podendo interferir de modo direto na qualidade do autocuidado, uma vez que o não entendimento das orientações realizadas nos cuidados paliativos, podem causar ansiedade e insegurança na realização do cuidado, aumentando os desfechos clínicos negativos. As evidências apresentadas pelo estudo, dispõe que grande parte da população em fase paliativa com letramento em saúde limitado, pode ter divergência no entendimento das informações transmitidas pelos prestadores de cuidado.…”
Section: Resultsunclassified
“…O estudo considera que o letramento em saúde com base em evidências inserido na população em fase paliativa pode melhorar a resposta de aceitação do paciente e da família, refletindo em uma tomada de decisão compartilhada, podendo seguir o melhor caminho para a fase final de sua vida (Harding et al, 2021).…”
Section: Resultsunclassified
“…Studies suggest that in India, the patients and their families often put the burden of the medical decision solely on the doctors' expertise and remain a passive audience to the decision-making process (Jacob, 2014;Sareen & Dutt, 2019). Various factors such as high financial burden of cancer, low education and knowledge about the disease, and low financial status that renders the possibility of taking second opinions impossible, were associated with the high prevalence of paternalistic decisionmaking (Harding et al, 2022;Mathew et al, 2020). Conversely, patients with higher socioeconomic status and greater literacy levels were more actively involved in the decision process (Datta et al, 2017;Harding et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Various factors such as high financial burden of cancer, low education and knowledge about the disease, and low financial status that renders the possibility of taking second opinions impossible, were associated with the high prevalence of paternalistic decision-making (Harding et al, 2022; Mathew et al, 2020). Conversely, patients with higher socioeconomic status and greater literacy levels were more actively involved in the decision process (Datta et al, 2017; Harding et al, 2022). Such findings indicate that contextual constraints of the patients and family caregivers are fused with and inevitably shape their decision-making style (Blok et al, 2023; Datta et al, 2017; Ram Prakash & Lingam, 2021; Zafar & Peppercorn, 2023).…”
Section: Introductionmentioning
confidence: 99%